Nucleation and Grain Boundary Evolution in Dynamic Recrystallization of 316LN Steel During Hot Deformation - Liu, Jiachen; Chen, Huiqin (Frontiers in Materials, 2019)
In this work, dynamic recrystallization (DRX) behavior of 316LN austenitic stainless steel was studied by hot compression experiments at temperature range of 900~1200℃ and strain rate range of 0.005~0.5 s−1. The Arrhenius hyperbolic sine function was given to fit well with the hot deformation flow behavior of 316LN steel and the average activation energy (Q) was obtained. The variation of DRX fraction and average grain size was studied and modeled. Microstructural evolution of 316LN steel during hot deformation in condition of 1100℃ and 0.05s-1 was studied by EBSD analysis. It was found that twining plays a significant role in nucleation and growth of DRX during hot deformation. The nucleation of DRX in 316LN steel was characterized by bulging of serrated grain boundaries. Twining took place near the serrated grain boundary in large amount, accelerating the separation of bulging from deformed parent grains to form DRX nucleus. At the steady state strain, uniformly refined DRX grains almost took charge of the microstructure of 316LN steel.